Increasing Profit-Sharing Financing by Tax Incentive Schemes Similar to Venture Capital Companies - Muhammad Rifky Santoso (Politeknik Ganesha Medan, 2026)
Financing with a profit loss sharing (PLS) scheme has a more positive and significant impact on economic growth compared to that of credit distribution by conventional banks. Financing with a PLS scheme has a high risk, so Islamic banks are careful in increasing this financing. Therefore, incentives are needed to increase this financing. This article used the grounded theory method. Grounded theory is not a theory but a method and a research strategy that aims to produce a theory from data. This article proposes a PLS financing scheme with income tax. Substantively, the PLS financing scheme is like the financing carried out by a venture capital company. With some requirements, the income received by the venture capital company is nontaxable. Therefore, income from financing carried out by Islamic banks that is similar to financing from venture capital companies can be non-taxable, of course, with the same requirements. Affirmation regulations are needed to strengthen the provision of incentives to Islamic banks so that their income is not subject to tax. Increasing financing with a PLS scheme provides benefits by maintaining religion, soul, mind, descendants, and property. In the short term, this income tax incentive harms state revenues, but in the long term, it will have a positive impact by increasing value-added tax and income tax from financing recipients.